Design and analysis of different cooling schemes of a flux‐modulated permanent magnet in‐wheel motor for electric vehicle applications. Issue 3 (24th January 2021) - Li, Longnv; Zhu, Gaojia; Zhao, Yishuang; Jia, Nan; Xue, Ming; Li, Yanbing
Abstract: The flux‐modulated permanent magnet (FMPM) in‐wheel motor has provided a promising solution to drive electric vehicles (EVs) because of its salient features such as tight structure, high power (torque) density, and high transmission efficiency. But it easily causes excessive temperature rise and limits the torque output due to the poor heat dissipation capacity inside the in‐wheel cavity. In this regard, a 3D fluidic‐thermal coupled model integrating computational fluid dynamics and numerical heat transfer is proposed and validated by experimental results on a 2.1 kW, 1800 rpm PM motor prototype. The temperature rise distribution of a 22.6 kW, 600 rpm FMPM in‐wheel motor under an existing natural cooling structure is then numerically investigated. It is revealed that it is difficult to satisfy the thermal requirements of the motor using only natural cooling approach. Consequently, a self‐ventilated cooling system and a non‐contact lead‐in (NCLI) system are used to maintain the temperature rise. In addition, to further improve the heat dissipation capacity, the NCLI structure is modified with water cooling channels separated by orifice plates to limit the excessive motor temperature rise. The motor temperature rises under different cooling schemes are analyzed to verify the effectiveness of the proposed cooling structures.